1995
DOI: 10.1111/j.1365-2125.1995.tb04451.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and adverse reactions after a single dose of pentamidine in patients with Trypanosoma gambiense sleeping sickness.

Abstract: 1 Plasma concentrations of pentamidine were measured up to 1-8 months after a single 2 h i.v. infusion of 3.0 to 4.8 mg kg-1 pentamidine isethionate in 11 patients with late stage Trypanosoma gambiense sleeping sickness. 2 Maximum plasma drug concentrations varied between 713 and 2461 nmol 1-1.After termination of infusion, a rapid distribution phase over 10 min was followed by a slower distribution phase and an elimination phase prolonged over weeks to months. 3 The 'terminal'"elimination rate constant could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…S2). 39 Pentamidine is administered during early stage disease; whereas, melarsoprol or a combination of nifurtimox/eflornithine are used during the late stage. These drugs are not only difficult to administer but also toxic, in particular the arsenical melarsoprol provokes fatal outcomes in 10% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…S2). 39 Pentamidine is administered during early stage disease; whereas, melarsoprol or a combination of nifurtimox/eflornithine are used during the late stage. These drugs are not only difficult to administer but also toxic, in particular the arsenical melarsoprol provokes fatal outcomes in 10% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The stable very low relapse rate, despite the extensive former use in prophylaxis programmes (Waddy, 1970), may be due to the uptake of the molecule by three different transporters (Barrett et al 2007). Pharmacokinetic evidence indicates that three injections may be equally effective (Bronner et al 1991;Bronner, 1994) and a respective comparative clinical trial is currently ongoing to evaluate this (ISRCTN55042030). Due to the high potency of pentamidine and the low drug levels detected in the CSF (Bronner et al 1991) the use to treat 'intermediate stage' patients (up to 10 or 20 white blood cells (WBC) mm − 3 in CSF) was suggested (Doua et al 1996).…”
Section: P E N T a M I D I N Ementioning
confidence: 99%
“…Pharmacokinetic evidence indicates that three injections may be equally effective (Bronner et al 1991;Bronner, 1994) and a respective comparative clinical trial is currently ongoing to evaluate this (ISRCTN55042030). Due to the high potency of pentamidine and the low drug levels detected in the CSF (Bronner et al 1991) the use to treat 'intermediate stage' patients (up to 10 or 20 white blood cells (WBC) mm − 3 in CSF) was suggested (Doua et al 1996). The resulting efficacy in respective studies is equivocal (Ruiz et al 2002;Lejon et al 2003;Balasegaram et al 2006b).…”
Section: P E N T a M I D I N Ementioning
confidence: 99%
“…Interestingly, it has been demonstrated that pentamidine may accumulate in rat liver lysosomes [14], the niche of intracellular multiplication of T. whipplei, which may explain why the MICs observed in cell culture assay tend to be lower compared with the axenic medium assay, and why pentamidine was effective in vitro against C. burnetii in cells. MICs against T. whipplei in the current study were lower compared with plasma concentrations of pentamidine, which have been reported to range from 0.25 mg/L to 8.0 mg/L during treatment of Trypanosoma gambiense infections [15]. Pentamidine is known to have a large volume of distribution and a very long elimination half-time that reflect the pronounced tissue affinity of the drug.…”
Section: Discussionmentioning
confidence: 76%